The Enhancement of Leg Muscle Strength by Back Half Squat and Leg Extension Practice towards Long Range Kicking Ability of Soccer Player - Podung, Beatrix J.; Paturusi, Achmad; Kawuwung, Weliam (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to measure how influential the enhancement of leg muscle strength by back half squat and leg extension practice towards long range kicking ability of Sea Horse soccer player. The population is all soccer player in “PS Seahorse Partners” soccer association. 20 respondents as sample were picked by “Random Sampling” technique. Sample is divided into two group through “Matched Ordinal Pairing” technique in which 10 respondents for leg muscle strength exercise with half squat and other 10 respondents do leg extension exercise (comparison). Used method in this research is experimental method, “randomized control group pre-test ad post-test design” as the research design. Research instrument used in this research is “kick ability test”. To examine the hypothesis t-test is used based on two independent samples by real standard α=0,05. T-test score obtained from the calculation result using t-test statistics is tob = 10,66. While score obtained from t table critical score with real standard α = 0,05; n1+n2-2 is as ttab = 2,101. This fact shows that tob = 10,66 > ttab = 2,101, so zero hypothesis(o) is refused and accepting the alternative hypothesis (Ha), which clarifies that the ability average of long range kick in back half squat exercise group that treated by leg muscle strength exercise is bigger than the ability average leg extension exercise group. So, the finding shows that leg muscle strength exercise with back half squat is better in enhancing the log range kicking ability of Seahorse Partners soccer player compared to leg extension exercise group.